A Contextual Study of Brass Band Music within the Peki-Kpando Area of the Volta Region of Ghana - Wuaku, H.M. (University of Ghana, 2015)
Brass band music forms a very important part of the musical culture of the Volta Region of Ghana. As a legacy of the activities from post-colonial Ghana, brass bands generally include European brass and percussion instruments with occasional addition of local drums and other exotic instruments of the tradition as a result of indigenization. The purpose of the study is to investigate the contextual use of brass bands in funerals, festivals and state functions in the Mid-Eweland of the Volta Region of Ghana. The sample for the study comprised selected brass bands within Peki, Kpando, Alavanyo and Ho. Specifically, ten (10) bands were visited for the study. Participant-observation, interview, field recording and musical transcriptions were tools used for data collection. The study revealed repertoire decisions, instrumentation templates, costume, and performance styles of the brass bands within the three contexts under review. It also pointed out the traditional musical elements employed in indigenizing funeral hymns and popular songs as part of their re-constructional processes. To be able to fulfil the indigenization dream, it is suggested that an eclectic collection of traditional instruments are made by band directors so they can play all indigenous traditional genres. Finally, it recommends that other band masters and future researchers emulate the examples of the Volta Region bands.
Thesis(PHD)-University of Ghana, 2015
Keywords: Brass Band Music; Peki-Kpando Area; Volta Region